UMHMF KPHA Breastfeeding Grant: Internship Report - Kaur, Ramandeep (My University, 2013)
The report presents the tasks completed during internship at KPHA which are listed below: • Preparing a report stating the implementation of UMHMF/KPHA grant in 23 counties of Kansas. • Interacting with grantees from 23 County Health Departments and various officials from State Health Department and WIC program. • Participating and organizing sessions at KPHA Annual Fall Conference 2012. All of these tasks have been completed successfully. The workshop session was attended by representatives from 17 counties in Kansas. The activities related to the grant were coordinated by interacting with the 23 county health departments via e-mails. An half-yearly report of the grant analyzing progress of 23 grantee counties was prepared and submitted to the grantors at UMHMF.
Keywords: Breastfeeding; Public Health; WIC Program; Public Health (0573)